2013
DOI: 10.1002/jor.22320
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial‐derived reactive oxygen species (ROS) play a causal role in aging‐related intervertebral disc degeneration

Abstract: Oxidative damage is a well-established driver of aging. Evidence of oxidative stress exists in aged and degenerated discs, but it is unclear how it affects disc metabolism. In this study, we first determined whether oxidative stress negatively impacts disc matrix metabolism using disc organotypic and cell cultures. Mouse disc organotypic culture grown at atmospheric oxygen (20% O2) exhibited perturbed disc matrix homeostasis, including reduced proteoglycan synthesis and enhanced expression of matrix metallopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 40 publications
5
128
0
Order By: Relevance
“…Here, we identified FOXO3 as a novel mediator of NP cell adaptation to hypoxia and demonstrated that FOXO3 and, to a lesser extent, FOXO1 regulate the expression of autophagy genes and activation in NP cells. Although a causal relationship between autophagy defects and IDD has not yet been established, our findings showed that FOXO function promotes NP cell survival under oxidative and inflammatory stresses, major drivers of NP cell apoptosis and aging‐related IDD (Nasto et al, 2013; Wang et al, 2013; Yang et al, 2014), and thus suggest that activation of FOXO in aged IVD could increase autophagy and protect NP cells from stress‐induced apoptosis. Further supporting this hypothesis, various studies have shown that autophagy activation can protect NP cells against different apoptotic insults (Jiang, Jin, Wang, Jiang, & Dong, 2014; Jiang, Zhang, et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…Here, we identified FOXO3 as a novel mediator of NP cell adaptation to hypoxia and demonstrated that FOXO3 and, to a lesser extent, FOXO1 regulate the expression of autophagy genes and activation in NP cells. Although a causal relationship between autophagy defects and IDD has not yet been established, our findings showed that FOXO function promotes NP cell survival under oxidative and inflammatory stresses, major drivers of NP cell apoptosis and aging‐related IDD (Nasto et al, 2013; Wang et al, 2013; Yang et al, 2014), and thus suggest that activation of FOXO in aged IVD could increase autophagy and protect NP cells from stress‐induced apoptosis. Further supporting this hypothesis, various studies have shown that autophagy activation can protect NP cells against different apoptotic insults (Jiang, Jin, Wang, Jiang, & Dong, 2014; Jiang, Zhang, et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…Aging model mice are characterized by an increased concentration of ROS and a significant reduction in their antioxidant defenses (32). ROS are chemically reactive oxygen-derived molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [3] found that oxidative stress caused apoptosis of rat notochordal cells via both intrinsic and extrinsic pathways. Nasto et al [4] found that mitochondrial-derived reactive oxygen species play a causal role in age-related intervertebral disc degeneration.Third, antioxidants may be a novel treatment option for disc degeneration. Recent studies have shown that ferulic acid (FA) [5] and resveratrol possess excellent antioxidant and antiinflammatory properties, can treat nucleus pulposus cells from the damage caused by oxidative stress and may have considerable promise in the treatment of disc degeneration.…”
mentioning
confidence: 99%
“…Kim et al [3] found that oxidative stress caused apoptosis of rat notochordal cells via both intrinsic and extrinsic pathways. Nasto et al [4] found that mitochondrial-derived reactive oxygen species play a causal role in age-related intervertebral disc degeneration.…”
mentioning
confidence: 99%